Hubungan Pengetahuan Gizi Seimbang Dengan Status Gizi Remaja Putri di SMA Negeri 4 Manado : The Relationship of Balanced Nutrition Knowledge with the Nutritional Status of Young Women at SMA Negeri 4 Manado - Gabriella Dameria Siregar; Nova Hellen Kapantow; Maureen I Punuh (JPAI: Jurnal Perempuan dan Anak Indonesia, 2023)
Nutritional status is an essential factor in determining the quality of life, normal nutritional status is achieved if nutritional needs are met. Nutritional problems that occur in adolescents will have an impact on nutritional status and health problems including adolescent girls. If teenage girls do not consume nutritious food, it will result in a lack of endurance so that they are susceptible to disease. One of the factors that affect nutritional status is knowledge of balanced nutrition. Good nutritional knowledge affects a person's intake through the selection of nutritious foods they consume in order to achieve good nutritional status. This study aims to determine the relationship between balanced nutritional knowledge and the nutritional status of adolescent girls at SMA Negeri 4 Manado. This type of research is an analytic quantitative research using a cross-sectional study approach. The research time was conducted in May 2023. The sample of this study were female students at SMA Negeri 4 Manado in classes X and XI with a total of 100 respondents. The results of this study showed that the knowledge score was not good for as many as 52 female students and the knowledge score was good for as many as 48. The majority of respondents' nutritional status at SMA Negeri 4 Manado was categorized as good (standard) as many as 74. The conclusion of this study is that there is no relationship between balanced nutrition knowledge and the nutritional status of adolescent girls with a p-value = 0.597.   ABSTRAK Status gizi menjadi faktor penting dalam menentukan kualitas hidup, status gizi normal tercapai apabila kebutuhan gizi terpenuhi. Masalah gizi yang terjadi pada remaja akan berdampak pada status gizi dan masalah kesehatan termasuk remaja putri. Apabila remaja putri kurang mengonsumsi makanan yang bergizi maka mengakibatkan daya tahan tubuh yang kurang sehingga mudah terserang penyakit. Faktor yang mempengaruhi status gizi salah satunya pengetahuan gizi seimbang. Pengetahuan gizi yang baik mempengaruhi asupan seseorang melalui pemilihan makanan bergizi yang dikonsumsinya agar dapat mencapai status gizi yang baik. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan gizi seimbang dengan status gizi remaja putri di SMA Negeri 4 Manado. Jenis penelitian ini adalah penelitian kuantitatif bersifat analitik dengan menggunakan pendekatan cross sectional study. Waktu penelitian dilakukan pada bulan Mei 2023. Sampel pada penelitian ini adalah siswi di SMA Negeri 4 Manado pada kelas X dan kelas XI dengan jumlah 100 responden. Hasil penelitian ini menunjukkan bahwa skor pengetahuan tidak baik berjumlah 52 siswi dan skor pengetahuan baik berjumlah 48 siswi. Mayoritas status gizi responden di SMA Negeri 4 Manado berkategori baik sebanyak 74 siswi. Kesimpulan dari penelitian ini yaitu tidak terdapat hubungan antara pengetahuan gizi seimbang dengan status gizi remaja putri dengan nilai p = 0,597.